PENGARUH KESENIAN TARI GANDRUNG SEBAGAI SARANA PERKEMBANGAN BAKAT PERSERTA DIDIK SMP DI KABUPATEN BANYUWANGI - Ivan Rizki Fauzi; Gesta Pramatasari; Kharisma Husnul Khotimah; Najma Fatimatuz Zakiyah; Firdha Yusmar; I Ketut Mahardika; Rizka Elan Fadilah (FKIP e-PROCEEDING, 2022)
The purpose of this study is to describe the Gandrung Dance in Banyuwangi City, East Java Province, in order to make it easier for students to develop Gandrung Dance art and can be a learning medium for all. The research methods used are the background, the history of the development of Gandrung art, and the form of presentation in Banyuwangi Regency using qualitative descriptive methods. Gandrung dance itself is a dance performed by adults, it can also be performed by Junior High School Students in Banyuwangi Regency. The dance is performed in a solo or group form. Jejer Gandrung dance type there are three floor patterns including circles, squares, and lines. In the Jejer Gandrung Kembang Menur dance, there are four floor patterns including: Trapezoidal, circle, straight line, and curved. Likewise, Gandrung Dor dance has seven floor patterns including curved lines, straight lines, rhombuses, trapezoids, parallelograms, and circles.